Ascenso y declive de la Policía de Narcóticos del Departamento de Salubridad Pública en México (1917-1960) - Pérez Ricart, Carlos A.; Olvera Hernández, Nidia A. (El Colegio de México, A.C., 2021)
This article traces the emergence, rise and fall of the police bureau in charge of substance control within the Public Health Department (Departamento de Salubridad Pública, or DSP, later the Secretaría de Salubridad y Asistencia, or SSA) between 1917 and the early 1960s. It examines the origins and organizational changes of the narcotics police, the practices used by their agents in the enforcement of the laws of their time and the reasons for their slow but progressive loss of importance going into the 1940s, during which time they began to be replaced by the Judicial Police, under the Attorney General of the Republic, the army and local police forces. This article also presents a case study of the paradigm shift in which the Mexican state gradually modified its interpretation of the drug problem, which went from being a public health issue to one that was codified in terms of security.The primary documentary basis for this article is the History Archive of the Health Secretariat (Archivo Histórico de la Secretaría de Salud, or AHSSA), which conserves the reports of the dsp’s Narcotics Police as well as records on their personnel.